PENGARUH BERBAGAI KONSENTRASI INOKULUM Lactobacillus plantarum TERHADAP TINGKAT KELANGSUNGAN HIDUP IKAN PATIN (Pangasius hypophthalmus Sauvage) - Atira Atira (Universitas Tadulako, 2009)
The objective of this research was to find out the maximum concentration of L. plantarum inoculums capable of sustaining 100% survival of catfish. The research was conducted by laboratory experiments using a Completely Randomized Design method. The experimental results were examined by Analysis of Variance and an Advanced Duncan’s double test. The inoculums concentrations were 0, 10, 20, 40, and 80 mL/2 L water. Each treatment was repeated three times. The catfish for the experiment was 2 months old, length about 6 cm, and weight about 2 g. Every aquarium in the experiment contained 2 L of water. The testing parameter was the number of fish that can survive for five days. Additional experimental data obtained was the water quality (DO, pH, temperature, ammoniac, and nitrate). The experimental results showed that 100% survival of catfish occurred in the inoculums concentrations of 0 (kontrol), 10, and 20 mL. At the inoculums concentrations of both 40 and 80 mL, the catfish survival were greatly reduced to only 8.33 and 0%, respectively.